Design of Information Systems Inventory Inventory In Sinar Sakti Racing Industry Based Web: Design of Information Systems Inventory Inventory In Sinar Sakti Racing Industry Based Web - Joko Saputro; Veronica Septaningsih (Institute of Computer Science (IOCS), 2020)
Inventory Information System Design is a design system that supplies information to many process that consists of stock, inventory and reports. Therefore, it is necessary to make the Inventory Information System applications to support the company's performance manual was originally turned into a computerized system to generate reports that more rinci.Pengembangan applications is done by collecting data, system planning, system analysis, system design and development base data.Pemrograman applications developed in PHP. Development of the database used is MySQL and scripts developed by Sublime.Dapat concluded that the design and implementation of information system in Company Sinar Sakti Inventory Insdustry Racing has its dikembangkan.Dengan designed this system in the Company Sinar Sakti Racing Industry,